2016
DOI: 10.1002/adhm.201600342
|View full text |Cite
|
Sign up to set email alerts
|

Functional Supramolecular Polymers: A Fluorescent Microfibrous Network in a Supramolecular Hydrogel for High‐Contrast Live Cell‐Material Imaging in 3D Environments

Abstract: A new bottom-up strategy based on aromatic peptide amphiphile is developed for a high-contrast visualization of 3D live cell-material imaging-something that has been difficult to achieve previously because of the problems associated with the diffraction of light by the nanosized peptide materials and the aggregation-caused quenching of aggregated π-conjugated fluorophores in the nanostructures. This study reports an example of a novel supramolecular hydrogelator, naphthaleneimide-phenylalanine (NI-Phe), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…[2d, 6] In particular, the use of an aphthaleneimide N-cap led to fluorescent fibrils,w hich could be used for imaging purposes. [7] Alternatively,p yrene was successfully applied to obtain at ryptophan-based gel in phosphate buffer at neutralp Hf or encapsulationo fb iomolecules. [8] Alkyl-chain Nacylationsh ave also been explored, althoughp rediction of the supramolecular behavior of these derivativesi sf ar from trivial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2d, 6] In particular, the use of an aphthaleneimide N-cap led to fluorescent fibrils,w hich could be used for imaging purposes. [7] Alternatively,p yrene was successfully applied to obtain at ryptophan-based gel in phosphate buffer at neutralp Hf or encapsulationo fb iomolecules. [8] Alkyl-chain Nacylationsh ave also been explored, althoughp rediction of the supramolecular behavior of these derivativesi sf ar from trivial.…”
Section: Introductionmentioning
confidence: 99%
“…Different examples have been described to date, with fluorenylmethyloxycarbonyl (Fmoc) being the most popular appendage, followed by naphthalene . In particular, the use of a naphthaleneimide N‐cap led to fluorescent fibrils, which could be used for imaging purposes . Alternatively, pyrene was successfully applied to obtain a tryptophan‐based gel in phosphate buffer at neutral pH for encapsulation of biomolecules .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tao Yi and coworkers have studied gelation behaviors of NI compounds and they found that materials displayed high fluorescence quantum yields in both solution and solid‐state . Recently we reported a NI‐based supramolecular hydrogelator, which exhibits AIE phenomenon . Particularly, we have shown the self‐assembly of NI−F that results in the formation of AIE‐active microfibers which facilitate the high contrast visualization of 3D live cell imaging .…”
Section: Resultsmentioning
confidence: 99%
“…Supramolecular hydrogels of many reported peptide molecules self-assembled into nanofibrillar morphology with the smallest possible width size, which is much less than 50 nm. [27] Few examples of higher-order self-assembled aggregates are also known in the literature. [19,38,39] Understanding the selfassembly mechanism for the formation of such large aggregates is of significant importance but remains challenging.…”
Section: Self-assembly Of Dipeptide-based Compoundsmentioning
confidence: 99%
“…Examples of supramolecular chemistry include molecular self‐assembly, host–guest complexes, and mechanically interlocked molecular structures . Supramolecular hydrogels have been used in a variety of biomedical applications, including but not limited to imaging, tissue engineering, and therapeutic delivery . The injectable nature of supramolecular hydrogels makes them particularly attractive for clinical translation since they can be delivered using minimally invasive approaches.…”
Section: Introductionmentioning
confidence: 99%